Report on Abstracts of the 15th Meeting of IIM, the Interuniversity Institute of Myology - Assisi (Italy), October 11-14, 2018 - Davide Gabellini; Antonio Musarò (PAGEPress Publications, 2018)
On October 11-14, 2018, the 15th Meeting of the Interuniversity Institute of Myology (IIM) took place in the city Assisi, Italy. Muscle researchers from Italy, and various European and North-American countries gathered to discuss recent results on the physiology and diseases of skeletal muscle. The program showcased keynote lectures from world-renowned international speakers presenting advances in muscle stem cells, circadian rhythm, organismal development and growth, muscle physiology, and bioengineering. Novel, unpublished results from young trainees were presented as oral communications or posters, based on selection from submitted abstracts. Young trainees where directly involved in several aspects of the meeting by being responsible of organizing a scientific session, arranging three round tables tailored to the interests of their peers and chairing all scientific sessions. The meeting offered a unique opportunity for young researchers to present their work, have feedback from more experienced colleagues and establish collaborations to further understanding of muscular diseases and develop therapeutic strategies. The open, informal and friendly atmosphere of the meeting stimulated lively discussions, instrumental to highlight key areas of muscle research and foster scientific cross-fertilization and new collaborations. The meeting was very successful. A sign that the IIM community will continue to deliver important contributions to the training of young students and fellows, promoting our understanding of muscle formation and activity, the mechanism of muscle diseases and the progress toward therapeutic approaches. The Myology field is strong and articulated in basic, translational and early clinical research, moving toward the development of treatments for several muscle diseases as documented by the abstracts of the IIM meeting.